Neck Circumference Is Associated with Muscle Sympathetic Nerve Activity in Overweight and Obese Men but Not Women - Straznicky, Nora E.; Grima, Mariee T.; Sari, Carolina I.; Eikelis, Nina; Nestel, Paul J.; Dixon, John B.; Lambert, Gavin W.; Schlaich, Markus P.; Phillips, Sarah E.; Lambert, Elisabeth A. (Frontiers in Physiology, 2017)
Background: Neck circumference (NC) is a predictor of cardiometabolic risk. The objective of this study was to explore the relationship of NC to muscle sympathetic nerve activity (MSNA) within an overweight and obese population. Methods: The study design was a retrospective cross-sectional analysis. Un-medicated persons (72 men, 53 postmenopausal women) aged 56 + 1 years (mean + SEM) with body mass index (BMI) 32.8 + 0.4 kg/m2, were studied. NC was measured together with traditional anthropometric measures, supine blood pressure, fasting blood lipids, insulin and glucose. Insulin sensitivity was assessed by homeostasis model (HOMA-IR) and Matsuda Insulin Sensitivity Index (ISI) derived from 75-g oral glucose tolerance test. Resting multiunit MSNA was recorded by microneurography in the peroneal nerve and expressed as burst frequency and burst incidence. Results: Men within the highest tertile of NC had significantly higher fasting and post-glucose plasma insulin levels (insulin AUC0-120), HOMA-IR, non-esterified fatty acids, MSNA (45 + 2 versus 36 + 2 bursts per min; 69 + 3 versus 58 + 3 bursts per 100hb) and heart rate, and lower Matsuda ISI compared to men in the lowest tertile (P all <0.05). In stepwise regression analyses, NC alone explained 12%, and together with insulin AUC0-120 it accounted for 22%, of the variance in MSNA in men. In women, NC was associated with anthropometric measures but not with MSNA or metabolic indices. Conclusions: Among overweight and obese men, NC was independently associated with elevated MSNA and hyperinsulinemia, and thus may be relevant to cardiometabolic risk prediction. The biological basis of gender differences merits further elucidation.